Global trends and research frontiers on heat stress in poultry from 2000 to 2021: A bibliometric analysis - Uyanga, Victoria Anthony; Musa, Taha H.; Oke, Oyegunle Emmanuel; Zhao, Jingpeng; Wang, Xiaojuan; Jiao, Hongchao; Onagbesan, Okanlawon M.; Lin, Hai (Frontiers in Physiology, 2023)
Heat stress remains a major environmental factor affecting poultry production. With growing concerns surrounding climate change and its antecedent of global warming, research on heat stress in poultry has gradually gained increased attention. Therefore, this study aimed to examine the current status, identify the research frontiers, and highlight the research trends on heat stress in poultry research using bibliometric analysis. The literature search was performed on the Web of Science Core Collection database for documents published from 2000 to 2021. The documents retrieved were analyzed for their publication counts, countries, institutions, keywords, sources, funding, and citation records using the bibliometric app on R software. Network analysis for co-authorship, co-occurrence, citation, co-citation, and bibliographic coupling was visualized using the VOSviewer software. A total of 468 publications were retrieved, and over the past two decades, there was a gradual increase in the annual number of publications (average growth rate: 4.56%). China had the highest contribution with respect to the top contributing authors, collaborations, funding agencies, and institutions. Nanjing Agricultural University, China was the most prolific institution. Kazim Sahin from Firat University, Turkey contributed the highest number of publications and citations to heat stress in poultry research, and Poultry Science was the most productive and the most cited journal. The top 10 globally cited documents mainly focused on the effects of heat stress, alleviation of heat stress, and the association between heat stress and oxidative stress in poultry. All keywords were grouped into six clusters which included studies on “growth performance”, “intestinal morphology”, “heat stress”, “immune response”, “meat quality” and “oxidative stress” as current research hotspots. In addition, topics such as; “antioxidants”, “microflora”, “intestinal barrier”, “rna-seq”, “animal welfare”, “gene expression”, “probiotics”, “feed restriction” and “inflammatory pathways” were identified for future research attention. Therefore, this bibliometric study provides a detailed and comprehensive analysis of the global research trends on heat stress in poultry over the last two decades, and it is expected to serve as a useful reference for potential research that will help address the impacts of heat stress on poultry production globally.